Severe 25-Hydroxyvitamin D Deficiency May Predict Poor Renal Outcomes in Patients With Biopsy-Proven Diabetic Nephropathy - Zhou, Ting; Shen, Li; Li, Ze; Jia, Junjie; Xing, Haifan; Wang, Niansong; Jiao, Qiong; Fan, Ying (Frontiers in Endocrinology, 2022)
Aims This study aims to investigate the role of 25-hydroxyvitamin D (25(OH)D) levels in predicting renal survival in biopsy-proven diabetic nephropathy (DN) with type 2 diabetes mellitus (DM). Methods In this retrospective study, a total of 161 biopsy-proven DN patients were enrolled and divided into four groups (normal group: 25(OH)D>20ng/ml; mild group: 10<25(OH)D ≤ 20ng/ml; moderate group: 5<25(OH)D ≤ 10 ng/ml; severe group: 25(OH)D ≤ 5 ng/ml). The effect of the 25(OH)D level on renal survival was evaluated by multivariate Cox regression. Results A total of 161 type 2 DM patients with biopsy-proven DN were enrolled in this study. Patients with lower 25(OH)D levels had higher serum creatinine, urinary albumin creatinine ratio (UACR), total cholesterol, and parathyroid hormone levels as well as lower estimated glomerular filtration rate (eGFR), hemoglobin, albumin, and calcium levels and were more prone to diabetic retinopathy (DR). Rather than proteinuria and renal function, glomerular class and interstitial fibrosis and tubular atrophy (IFTA) had a significant correlation with 25(OH)D levels. Multivariate Cox regression indicated that severe deficiency of 25(OH)D levels was associated with adverse renal outcomes. Compared to the level in the normal group, after adjusting for clinicopathological characteristics, a lower 25(OH)D level remained a risk factor for renal outcomes. The HRs were 3.446 (95% CI 0.366-32.406, p=0.279) for the mild group, 8.009 (95% CI 0.791-81.102, p=0.078) for the moderate group, and 14.957(95%CI 1.364-163.995, P=0.027) for the severe group. Conclusion Levels of 25(OH)D less than 5 ng/ml were correlated with worse renal function, more pathological injury and poorer renal prognosis in patients with biopsy-proven DN.